Malind-Papua Ethnomathematics: Kandara Musical Instrument as Learning Media for Geometry Concepts in Elementary School - Fredy Fredy; Lili Halimah; Yayuk Hidayah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
Each regions has a local culture that is the identity of the area. The Malind (Anim Ha) tribe as the original tribe of Merauke has a musical instrument that has a copyright kandara. Kandara was used as a musical accompaniment of dances and songs at traditional ceremonies. Kandara can be used as a learning media for the concept of geometry in elementary schools. This article aimed to describe the instrument of the musical instrument as an ethnomatematics of the Malind-Papua tribe that can be used as a learning medium for geometrical concepts in elementary schools. It was qualitative research using the ethnographic approach. Sampling using a cluster random sampling technique. The results showed that, the first ethnomatematics were found in parts of the kandara such as the handle or hands of the kandara, head, bodyor middle part and the tail of the kandara. Secondly, the musical instrument of kandara can be used as a learning medium to explain the concepts of geometry in elementary school in the form of the concept of angles, flat shapes (triangles, rectangles and circles) and building spaces (incised cones and tubes). Thirdly, ethnomatematics can be a learning material in elementary schools based on local culture, not only can help students understand mathematical concepts well but also maintain and respect the cultures of local communities (Malind tribe as an indigenous of Merauke). Keywords: Ethnomathematics, Kandara, Learning Media, Geometry Concepts